ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI PADA BUDIDAYA TAMBAK INTENSIF UDANG VANNAMEI DI KECAMATAN PUNDUH PEDADA KABUPATEN PESAWARAN LAMPUNG - Ilham Ramadhani; Rizki Adi Puspita Sari; Elpawati Elpawati (AGRIBUSINESS JOURNAL, 2018)
This study aims to (1) determine the factors that affect Vannamei shrimp in intensive pond, and (2) analyze the responses of Vannamei shrimp production to the factors of production. This research was conducted in the District Punduh Pedada Pesawaran, Lampung regency. Data were collected through interviews, questionnaires and direct observations. Multiple linear regression was employed to analyze the data. The results showed that the factors that influence the production of Vannamei shrimp are shrimp fries, feeds, water mills, and spacious pools. Production elasticity of Vannamei shrimp in the district Punduh are inelastics.